Perancangan Dan Pembuatan Desain UI/UX Aplikasi Simpora Dengan Figma - Mohamad Firdaus; Indra Bakti (ITB Ahmad Dahlan Jakarta, 2024)
Tanjung Pandan Customs Office as a state institution has the opportunity to compete with other customs offices in Indonesia, as an added value for the assessment of the Tanjung Pandan Customs office in its assessment in the Customs Institution. SIMPORA as an information system for Budget Absorption and Realization is made to meet these needs. The design of the application design in this study was built with Figma Application. by making a Software Design Design (DPPL), then followed by the results of the application interface is expected to make this application user friendly. This process is carried out so that with a good time frame and planning it can produce a good product as well. The results of the software interface are also equipped with design and application documentation which in the end goal is to give the Tanjung Pandan Customs office a winner in the competition between customs offices throughout Indonesia.